The effects of analogy and explicit instructions on 50-m sprint performance and kinematics - Low, Jeffrey Fook Lee (Tanjong Malim, 2021)
The effects of analogy and explicit instructions on 50-m sprint performance and kinematics by Low, Jeffrey Fook Lee